IL-1β As Mediator of Resolution That Reprograms Human Peripheral Monocytes toward a Suppressive Phenotype - Giesbrecht, Katharina; Eberle, Mariel-Esther; Wölfle, Sabine J.; Sahin, Delal; Sähr, Aline; Oberhardt, Valerie; Menne, Zach; Bode, Konrad A.; Heeg, Klaus; Hildebrand, Dagmar (Frontiers in Immunology, 2017)
During infection pathogen associated molecular patterns (PAMPs) activate immune cells to initiate a cascade of reactions leading to inflammation and the activation of the adaptive immune response culminating in the elimination of foreign pathogens. However, shortly after activation of the host defense machinery, a return to homeostasis is preferred to prevent inflammation-induced tissue damage. This switch from the initial immunogenic to the subsequent tolerogenic phase after clearance of the infection can be mediated through highly plastic peripheral monocytes. Our studies reveal that an early encounter with Toll-like receptor (TLR) 7/8-ligand R848 mediates a strong pro-inflammatory monocytic phenotype that primes its own reprogramming towards an immuno-suppressive one. Previously, we showed that these R848-treated antigen-presenting cells (APCs) fail to activate allogeneic T cells and induce Tregs through STAT3-dependent PD-L1. Here we further demonstrate that R848-treated APCs suppress CD3/CD28-mediated and dendritic cell (DC)-mediated T cell activation and that adenosine and IDO/Kynurenin pathways are involved in tolerance induction. Reprogramming of monocytes after R848 stimulation requires the pro-inflammatory cytokine IL-1β and a boosted IL-6 release. The subsequent autocrine prolonged activation of STAT3 induces direct upregulation of tolerogenic factors which finally downregulate proliferation of activated T cells and mediate Tregs. Thereby our study suggests that inflammatory cytokines such as IL-1β and IL-6 should be considered as mediators of resolution of inflammation.